Single‐Shot Ultraviolet Compressed Ultrafast Photography - Lai, Yingming; Xue, Yujia; Côté, Christian‐Yves; Liu, Xianglei; Laramée, Antoine; Jaouen, Nicolas; Légaré, François; Tian, Lei; Liang, Jinyang (Laser & photonics reviews, 2020)
Compressed ultrafast photography (CUP) is an emerging potent technique that allows imaging a nonrepeatable or difficult‐to‐produce transient event in a single shot. Despite many recent advances, existing CUP techniques operate only at visible and near‐infrared wavelengths. In addition, spatial encoding via a digital micromirror device (DMD) in CUP systems often limits its field of view and imaging speeds. Finally, conventional reconstruction algorithms have limited control of the reconstruction process to further improve the image quality in the recovered (x,y,t) datacubes of the scene. To overcome these limitations, this article reports a single‐shot UV‐CUP that exhibits a sequence depth of up to 1500 frames with a size of 1750 × 500 (x,y) pixels at an imaging speed of 0.5 trillion frames per second. A patterned photocathode is integrated into a streak camera, which overcomes the previous restrictions in DMD‐based spatial encoding and improves the system's compactness. Meanwhile, the plug‐and‐play alternating direction method of multipliers algorithm is implemented to CUP's image reconstruction to enhance reconstructed image quality. UV‐CUP's single‐shot ultrafast imaging ability is demonstrated by recording UV pulses transmitting through various spatial patterns. UV‐CUP is expected to find many applications in both fundamental and applied science. Single‐shot UV compressed ultrafast photography (UV‐CUP) is developed by integrating a patterned photocathode into a streak camera and by implementing the plug‐and‐play alternating direction method of multipliers algorithm in image reconstruction. UV‐CUP, exhibiting as the world's fastest single‐shot UV camera, has imaged dynamics of spatially modulated ultra‐short UV pulses at 0.5 trillion frames per second in real time.